1979
DOI: 10.1073/pnas.76.10.4887
|View full text |Cite
|
Sign up to set email alerts
|

Covalent structure of subunits of bacterial luciferase: NH2-terminal sequence demonstrates subunit homology.

Abstract: The heterodimeric subunit structure of bacterial luciferase was'demonstrated more than 10 years ago. The enzymes from both Beneckea harveyi and Photobacterium fischeri have since been studied in detail; they each consist of two nonidentical subunits, designated a and f. Both are required for bioluminescence activity, with the active center apparently confined to the a subunit. Amino acid sequence analysis-of the NH2 termini of the a and P subunits of the B. harveyi and P. fischeri luciferases not only confirms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Structural Similarities-There is extensive structural conservation between the ␣ and ␤ subunits confirming their common origin (4). The topology of the ␣ and ␤ subunits is identical, and the secondary structural elements align exactly with the sequence (Fig.…”
Section: ␣45mentioning
confidence: 78%
See 2 more Smart Citations
“…Structural Similarities-There is extensive structural conservation between the ␣ and ␤ subunits confirming their common origin (4). The topology of the ␣ and ␤ subunits is identical, and the secondary structural elements align exactly with the sequence (Fig.…”
Section: ␣45mentioning
confidence: 78%
“…All bacterial luciferases studied so far appear to be homologous, and all catalyze the same reaction: The reaction proceeds through a series of intermediates leading to the formation of a C4a hydroxyflavin (for review see Ref. 4). Light emission apparently occurs from this hydroxyflavin, which dehydrates to yield FMN.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…harveyi than to the p subunit of P. phosphoreum (Cohn et al, 1985;Johnston et ul., 1986;Soly et al, 1988). These similarities suggest that IuxF arose by gene duplication of luxB , as has been proposed for luxA and luxB (Baldwin et al, 1979;Foran and Brown, 1988). With regard to the function of LuxF, the N-terminal sequences of recently described non-fluorescent flavoproteins from P. phosphoreum and P. leiognathi (O'Kane ef al., 1987;Kasai et a/., 1987) are strikingly similar to the first 35 amino acid residues of these polypeptides, so luxF quite probably encodes a non-fluorescent flavoprotein Mancini et a/., 1989;Baldwin et al, 1989).…”
Section: Organization Of Lux Genes In Other Speciesmentioning
confidence: 99%
“…It has been suggested that the duplication may have arisen prior to the divergence of the lines leading to present-day luminescent bacteria. 10 The active site is thought to be on the a subunit. The LuxAB enzyme catalyses the oxidation of FMNH 2 (reduced flavin) and a long chain fatty aldehyde to oxidised flavin (FMN) and a long chain fatty acid respectively.…”
Section: 4mentioning
confidence: 99%